The Effect of Product Attributes and Product Quality on the Purchase Decision of Oppo Brand Smartphones at Duayu Cell Manna Bengkulu Selatan - Alek Oka Dinata; Oni Yulianti; Yanto Effendi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The purpose of this study was to determine the effect of product quality and product attributes on purchasing decisions for Oppo Brand Smartphones at Duayu Cell Manna Bengkulu Selatan. The sample in this study were 30 consumers who purchased the Oppo type A54 smartphone at Duayu Cell Manna Bengkulu. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of multiple linear regression calculations obtained multiple linear regression equation Y = 9.445 + 0.436X1 + 0.360X2 + e . The coefficient of determination of the value of R square is 0.589. This means that X1 (product attributes) and X2 (product quality), affect the purchase decision (Y) by 58.9% while the remaining 41.1% is influenced by other variables not examined in this study. The results of the F test show that the significance is 0.000 <0.05. Because the significance level is below 0.05, it shows that together X1 (product attributes) and X2 (product quality) have a positive and significant influence together on purchasing decisions (Y). Product attributes have a positive and significant influence on purchasing decisions, product quality has a positive and significant influence on purchasing decisions because the significant value is smaller than 0.05.